Synergistic analysis of wake effect of two cylinders on energy harvesting characteristics of piezoelectric flag. (March 2023) - Latif, Usman; Younis, M. Yamin; Idrees, Saad; Uddin, Emad; Abdelkefi, Abdessattar; Munir, Adnan; Zhao, Ming
Abstract: In this study, the effect of asymmetric wake flow regime of two side-by-side cylindrical bluff bodies on power output is experimentally examined by using a piezoelectric flag. Different synchronization modes of the flag with wake flow are observed. It is demonstrated that the streamwise gap between the flag and cylinders ( G x ), and the center-to-center gap between cylinders have a significant impact on the flag's dynamical behavior that results in a fluctuation in the power output of the piezoelectric flag. The levels of output power are analyzed by varying the G x and the cross-stream or lateral gap ( N/d ) between the two cylinders. N/d values from 1.0 to 2.0 for different values of G x (2.0 ≤  G x  ≤ 4.0) are experimentally tested. The comparison of the flapping response at each point is made to ascertain the impact of the harvester's dynamic behavior on the output energy. The power generated at each point is recorded for all cases and a comparative analysis is made to find the optimal configuration. Limited research is conducted in the past to enhance the energy output by using the bluff body with the improved wake dynamics. Hence, two cylinders are employed in a uniform flow and crosswise gap between cylinders is varied to change the characteristics of the wake region. The cylinder arrangement with N/d  = 1.0, shows continuous oscillations and higher output power persisting for 2.0 ≤ G x  ≤ 4.0. The monotonic rise in power output is observed till G x  = 4.0. The stated configurations with N/d  = 1.0 gives a significant advantage over a single-cylinder-based energy harvester as a kinetic source of fluid energy harvester from the flowing fluid. The output power became almost doubled with an increase of 95% approximately using side-by-side arrangement. Highlights: Two side-by-side cylinders are studied to enhance energy efficiency of piezo-flag systems. Gap between cylinders as well along with the gap distance and flow velocity were studied. Wake width was remarkably increased without having the effect of base suction on piezo-flag. Energy generation with higher frequency can be achieved with the jet flow by creating gap in-between cylinders. At the optimal arrangement there is approximately 4 times higher amplitude and power generated.